Socioeconomic characteristics and domestic work as correlates of family satisfaction in Hong Kong mothers of young children - Cerin, Ester; Zhang, Casper J.P.; Mellecker, Robin R.; Ming, Wai-kit; Barnett, Anthony (BMC public health, 2023)
Background Family life satisfaction is an important contributor to the mental health of mothers with young children, who are particularly vulnerable to various sources of stressors. However, there is a dearth of studies on this topic in this demographic, the determinants of which likely differ across geographical and cultural contexts. We examined indicators of maternal socioeconomic status (SES) and domestic help as correlates of family satisfaction in Hong Kong mothers of young children. Methods Mothers (N = 322) of young children (3-5 years old) were recruited from neighbourhoods stratified by SES and population density. They self-completed a survey containing items on socio-demographics, SES characteristics (including household income and maternal education and employment status), maternal family satisfaction and division of domestic work in the household and family. Confounder-adjusted associations of maternal SES indicators and participation in housework and childcare activities by various agents (e.g., mother, spouse, other residents) were estimated. We also estimated the moderating effects of household income on the associations between maternal employment and family satisfaction, and those of maternal employment on the associations between domestic work division and family satisfaction. Results Household income and maternal education were positively related to maternal family satisfaction. Mothers in part-time employment had lower family satisfaction than non-working mothers and mothers working full-time. The latter reported higher family satisfaction than non-working mothers only if their household income was below HK$ 15,000. Domestic work performed by non-residents was predictive of higher family satisfaction, while mothers' housework and child(ren) tutoring were predictive of lower family satisfaction. Only part-time employed mothers benefited from spouse's assistance with domestic work. The interaction effects of maternal employment status on the associations between the division of child tutoring and family satisfaction were complex. Conclusions In Hong Kong, mothers of young children with lower education and household income, who hold a part-time job and participate in housework and child tutoring activities have the lowest levels of family satisfaction and, hence, are at higher risk of mental health problems. Spouses' and non-resident family members' participation in domestic work, as well as the establishment of more family-friendly employment practices, may help mitigate this risk. Trial registration N/A. Keywords: Life satisfaction, Psychological wellbeing, Housework, Work-family relation, quality of life